The Role of Islamic Banks to Support Halal Industry in Indonesia: A Systematic Literature Review - Trimulato; Asyraf Mustamin; Khaliq Ahmad (IAIN Syekh Nurjati Cirebon, 2026)
Islamic banking in Indonesia plays a significant role in supporting the development of the halal industry, which encompasses various sectors. The distribution of Islamic bank financing for the productive sector has not been maximized. This research is guided by the approach of using the VOSviewer application to analyze the network of literature relevant to this topic. By using this method, this research can identify trends and relationships across previous studies on Islamic banking and the halal industry, and uncover research gaps that have not been widely explored. This research employed a qualitative approach, using a Systematic Literature Review (SLR), to examine the literature on Islamic banking and the halal industry. Data sources were obtained from the Publish or Perish application to extract bibliometric data, which was then analyzed using VOSviewer. The results showed that Islamic banking plays a strategic role in providing financing that supports the development of the halal industry, including working capital, investment, and related sectors. The policy implications are the importance of strengthening the synergy between the Islamic banking sector and the halal industry, as well as the need for more integrated policies to support the growth of the Islamic-based economy in Indonesia.